Improved and standardized method for assessing years lived with disability after injury - JA Haagsma; S Polinder; RA Lyons; J Lund; V Ditsuwan; M Prinsloo; JL Veerman; EF van Beeck
OBJECTIVE: To develop a standardized method for calculating years lived with disability (YLD) after injury. METHODS: The method developed consists of obtaining data on injury cases seen in emergency departments as well as injury-related hospital admissions, using the EUROCOST system to link the injury cases to disability information and employing empirical data to describe functional outcomes in injured patients. FINDINGS: Overall, 87 weights and proportions for 27 injury diagnoses involving lifelong consequences were included in the method. Almost all of the injuries investigated (96-100%) could be assigned to EUROCOST categories. The mean number of YLD per case of injury varied with the country studied. Use of the novel method resulted in estimated burdens of injury that were 3 to 8 times higher, in terms of YLD, than the corresponding estimates produced using the conventional methods employed in global burden of disease studies, which employ disability-adjusted life years. CONCLUSION: The novel method for calculating YLD after injury can be applied in different settings, overcomes some limitations of the method used to calculate the global burden of disease, and allows more accurate estimates of the population burden of injury.